Russian Caucasians have a higher risk of erosive reflux disease compared with East Asians: A direct endoscopic comparison. Issue 5 (12th December 2016) - Ko, S.‐H.; Baeg, M. K.; Jung, H. S.; Kim, P.; Choi, M.‐G.
Abstract: Background: Erosive reflux disease (ERD) is prevalent in the West, and its incidence is increasing in the East. The differences between the West and East, especially in body composition, have not been investigated thoroughly. Methods: Subjects who underwent esophagogastroduodenoscopy and body composition analysis during health screening were analyzed retrospectively. Russian Caucasians who visited Korea were propensity matched with native Koreans. Endoscopy results were analyzed to identify ERD and gastroesophageal flap valve (GEFV) status. Body composition and laboratory results were compared to identify risk factors for ERD. Key Results: 32 279 subjects underwent health screening with 1496 Russian Caucasians propensity matched with 1496 Koreans. ERD prevalence was 20.2% for Caucasians and 9.8% for Koreans ( P <.001). Caucasians had significantly greater body mass index (BMI) and were more sarcopenic. Significant risk factors for ERD were Caucasian ethnicity (OR 1.629, 95% CI 1.265–2.099, P <.001), male gender (OR 2.374, 95% CI 1.883–2.993, P <.001), greater BMI (OR 1.067, 95% CI 1.041–1.093, P <.001), and abnormal GEFV (OR 2.730, 95% CI 2.194–3.397, P <.001). H. pylori seropositivity (OR 0.614, 95% CI 0.488–0.774, P <.001) and atrophic gastritis (OR 0.547, 95% CI 0.411–0.728, P <.001) were significantly preventive. Conclusions & Inferences: Caucasian ethnicity is a significant risk factor for ERD. Greater BMI, male gender and abnormal GEFV are associated with ERD, and H. pylori seropositivity and atrophic gastritis are preventive. Further studies are needed to assess the differences in ERD between Caucasians and East Asians.